Idiopathic Thrombocytopenic Purpura as Initial Manifestation of Systemic Lupus Erythematosus: A Case Report - Fatih Bağcıer; Akın Erdal (Galenos Yayinevi, 2016)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that can affect almost any organ system. Its presentation and course are highly variable. The classic presentation of SLE in a woman of childbearing age is fever, arthritis, and malar rash triad. However, patients may present rare types of manifestations such as idiopathic thrombocytopenic purpura.